A ELEVEN-LEVEL GRID-CONNECTED CONVERTER TOPOLOGY FOR SINGLEPHASE TRANSFORMERLESS PV SYSTEMS - Naresh, B.; kumar, M.Vinay; Kumar, G.V.Nagesh (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
This paper is composed of three cascaded full bridges, these full-bridges needs a separate power supply in each full bridge section, the former is supplied by the PV generator and latter is supplied by a flying capacitor. The multilevel output diminishes the harmonic distortion and electromagnetic interference. The effectiveness of the proposed approach also minimizes the common mode leakage current with the help of transient circuit. The addition with the earlier switch another is connects the midpoint of dc-link to the converter output. Simulations show the effectiveness of the proposed solution.